A Review of Toyin Falọla. Cultural Modernity in a Colonized World: The Writings of Chief Isaac Oluwole Delanọ. Pan-African University Press, 2020, 739 pages. Toyin Falọla and Michael O. Afọlayan eds. Isaac O. Delanọ A Dictionary of Yoruba Monosyllabic Verbs Edited with an Introduction. Pan-African University Press, 2020, 538 pages. Toyin Falọla and Michael O. Afọlayan eds. Selected Works of Chief Isaac O. Delanọ on Yoruba Language Edited and Introduced. Pan-African University Press, 2020, 644 pages. - Bọla Dauda (Yoruba Studies Review)
Yes, the Yoruba Studies Review has asked me to write a “comprehensive review of the three books released on Chief Isaac Delanọ.” However, because Toyin Falọla had already committed 739 pages for an unsurpassed chronicle and review of the times, life, works, and classics of Doctor Isaac Oluwọle Delanọ, it would be pretentious of me to claim any attempt to do a comprehensive review of the three books. What I will do is to make a modest introduction Book Review 296 Bola Dauda of Delanọ’s long buried or an unheralded intellectual legacy. While Samuel Ajayi Crowther laid the foundation for the transition of Yoruba culture from oral to written literatures, Delanọ provided the guideline manuals, the methodological rubrics, and the compass and roadmaps for the studies and development of modern Yoruba orthography, linguistics, anthropological historiography, literatures, spirituality, and nation building. He was the first Administrative Secretary of the Ẹgbẹ Ọmọ Oduduwa, a cultural organization that became a political party in Nigeria at the dawn of Nigeria’s independence in the 1950s.